Die Informatik als Geisteswissenschaft - John Nerbonne (Zeitschrift für digitale Geisteswissenschaften)
The title of this paper indirectly refers to the theme of the 2014 Conference on Digital Humanities in German-Speaking Areas (Digital Humanities – methodischer Brückenschlag oder ›feindliche Übernahme‹?). I assume from this title that computer science is viewed as the originator of such a deliberate conquest. The first section of this paper explores how computer science, the headquarters of the enemy threatening to conquer our disciplines, also experienced and overcame an uncertain period of early development. The history of this discipline could serve as a source of inspiration or, at the very least, courage. The following section explores—as indicated by the title of this paper—how computer science could be viewed as a humanities discipline, including a historical perspective on the foundation of both disciplines or disciplinary fields. The historical dimension, but also the uncertainty, that is reflected in the conference theme serves as my starting point to present ten theses in the following section that explain the necessary factors for success if we wish to succeed with the Digital Humanities.